2022
DOI: 10.1155/2022/3217248
|View full text |Cite
|
Sign up to set email alerts
|

ASPM, CDC20, DLGAP5, BUB1B, CDCA8, and NCAPG May Serve as Diagnostic and Prognostic Biomarkers in Endometrial Carcinoma

Abstract: Uterine Corpus Endometrial Carcinoma (UCEC), the most common gynecologic malignancy in developed countries, remains to be a major public health problem. Further studies are surely needed to elucidate the tumorigenesis of UCEC. Herein, intersecting 203 differentially expressed genes (DEGs) were identified with the GSE17025, GSE63678, and e Cancer Genome Atlas-UCEC datasets. e Gene Ontology/Kyoto Encyclopedia of Genes and Genomes functional enrichment analysis and protein-protein interaction (PPI) network were p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 43 publications
0
1
0
Order By: Relevance
“…While CDC20 may be pro-oncogenic, it is unlikely to act in isolation, as at least 60 of the known 69 human APC substrates are associated with multiple cancer types when they accumulate [20], and are now considered a cancer signature [73,74]. A recent series of papers found that APC substrate-mRNAs, including HURP and CDC20, are elevated in multiple cancers, and are now recognized as a hub or signature gene set predictive of poor prognosis cancer (a subset of references are included here; [75][76][77][78]). These substrate accumulations are also associated with more aggressive cancers; in 182 breast tumor samples tested from high grade TNBC, 58% of the samples stained for G1 markers, yet expressed high levels of APC substrates, a cell cycle point when substrates should instead be degraded and at their nadir levels [28].…”
Section: Discussionmentioning
confidence: 99%
“…While CDC20 may be pro-oncogenic, it is unlikely to act in isolation, as at least 60 of the known 69 human APC substrates are associated with multiple cancer types when they accumulate [20], and are now considered a cancer signature [73,74]. A recent series of papers found that APC substrate-mRNAs, including HURP and CDC20, are elevated in multiple cancers, and are now recognized as a hub or signature gene set predictive of poor prognosis cancer (a subset of references are included here; [75][76][77][78]). These substrate accumulations are also associated with more aggressive cancers; in 182 breast tumor samples tested from high grade TNBC, 58% of the samples stained for G1 markers, yet expressed high levels of APC substrates, a cell cycle point when substrates should instead be degraded and at their nadir levels [28].…”
Section: Discussionmentioning
confidence: 99%
“…68 ASPM is a centrosomal protein that contributes to mitotic spindle formation, orientation, cytokines, neurogenesis, and brain development. 69,70 During metaphase, ASPM is located at the spindle poles, whereas during interphase, it is found in the nucleus and centrosome. Moreover, the ASPM localization to the midbody during cytokinesis suggests that it participates in abscission.…”
Section: Hmmrmentioning
confidence: 99%
“…72 Typically, ASPM has been extensively associated with autosomal primary microcephaly, a brain disorder characterized by a normal-appearing but small brain and mental retardation. 73 However, in the last decade, this gene has also been implicated in the progression of a variety of malignancies, 71 including glioblastoma, cancers of the prostate, breast, bladder, 74 and epithelial ovarian, 71,73 as well as endometrial, 69 hepatocellular, 75 lung, 76 and papillary renal cell carcinoma. 70 ASMP has been recognized by several authors as a significant prognostic gene in cases of BC.…”
Section: Hmmrmentioning
confidence: 99%